Sari Kedelai Kurma Meningkatkan Kadar Hemoglobin Pada Remaja Putri - Dewi, Yashinta Kumala; Handayani, Ririn; Anggraeni, Ernawati (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2024)
Anaemia often occurs in teenagers and young women due to nutritional problems. Iron, which is found in food nutrients, plays a significant role in the formation of haemoglobin. Soybeans and dates are some of the foods that contain high iron to elevate haemoglobin levels in the blood. Soybeans dan dates Juice is a drink that circulating and become popular in Indonesia. This study used the Pre-Experimental research type with a Group Pre-Post Test Design approach. Accidental sampling was used to select 18 respondents. The Paired T-test was used for data analysis. Before the participants were given date soybean juice, the average haemoglobin level in 18 respondents was 13.81 gr%. After drinking date soybean juice for six days, the haemoglobin level increased to 15.45 gr%. The difference in average before and after giving date soybean juice was 1.46 gr%. The results of the statistical tests with the Paired T-Test show a p-value of 0.001 < α = 0.05. This test concludes that Ha is accepted, which shows that giving date soybean juice has a positive effect on increasing haemoglobin levels in young women at Baitul Hikmah Tempurejo Vocational School. Therefore, young women should consider consuming date soybean juice to prevent anaemia.